2019
DOI: 10.1371/journal.pone.0216127
|View full text |Cite
|
Sign up to set email alerts
|

Preferences, use of and satisfaction with mental health services among a sample of Puerto Rican cancer patients

Abstract: Objective The purpose of this study was to describe the preferences, the use, satisfaction of mental health services (MHS) among a sample of Puerto Rican patients with cancer undergoing oncology treatment. Methods A convenience sample of 120 patients diagnosed with cancer was recruited. Self-report questionnaires assessed socio-demographic and background questions, and the Mental Health Service Preference, Utilization and Satisfaction Questionnaire (MHSPUS). The Socio-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Worldwide, over the last 20 years there has been increased interest in the use of measures of satisfaction in the assessment of healthcare delivery (Alazri & Neal, 2003; Carr‐Hill, 1992; Castro‐Figueroa et al., 2019; Fakhoury, 1998; Fan, Burman, McDonell, & Fihn, 2005; Jenkinson, Coulter, Bruster, Richards, & Chandola, 2002). Measures of patient satisfaction are now integral components of quality assurance in many healthcare systems (Department of Health (UK), 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, over the last 20 years there has been increased interest in the use of measures of satisfaction in the assessment of healthcare delivery (Alazri & Neal, 2003; Carr‐Hill, 1992; Castro‐Figueroa et al., 2019; Fakhoury, 1998; Fan, Burman, McDonell, & Fihn, 2005; Jenkinson, Coulter, Bruster, Richards, & Chandola, 2002). Measures of patient satisfaction are now integral components of quality assurance in many healthcare systems (Department of Health (UK), 2012).…”
Section: Introductionmentioning
confidence: 99%
“…17 Compounding this problem, Latinx contextual and cultural influences on caregivers present an unmet need for emotional support, 18 especially when Latinx individuals are less likely to have adequate access to culturally congruent psychosocial interventions. [19][20][21][22][23][24][25][26][27][28][29][30] Latinx cancer research had identified the psychosocial need of Latinx caregivers and described the importance of including psychosocial content related to communication and spirituality. [31][32][33] Contribution of caregivers to patient's well-being…”
Section: Introduction Patients With Advanced Cancer and Informal Care...mentioning
confidence: 99%
“…Although several psychotherapeutic interventions have been designed for advanced cancer ( Breitbart et al, 2018 ; Breitbart et al., 2012 ; Breitbart et al, 2010 ; Edmonds et al, 1999 ; Kissane et al, 2007 ; Lorenz et al, 2008 ; Luckett et al, 2011 ; Okuyama et al, 2017 ; Uitterhoeve et al., 2004 ), none of them have been developed or adapted for Latinos. Further, previous research has shown that Latinos diagnosed with cancer have less access to psychosocial and psychotherapeutic services ( Castro-Figueroa et al, 2019 ; Costas-Muñiz et al, 2020 ; Costas-Muniz et al, 2017 ; Luckett et al., 2011 ) and that multilevel and contextual factors (e.g., individual, provider, health system, and social) might influence the access to and uptake of psychosocial services for Latinos diagnosed with cancer ( Costas-Muñiz et al, 2020 ). Primary barriers to the access and use of psychosocial services in the general cancer patient population include having no perceived need for psychosocial services and support, lack of information or wanting more information about services ( Dilworth et al, 2014 ), uncertainty about the need for specialized mental health care, and the cost of such treatment ( Greenberg, 2004 ), receipt of support from other sources outside the cancer clinic, lack of awareness of services, and lack of provider referral ( Eakin & Strycker, 2001 ).…”
Section: Introductionmentioning
confidence: 99%